Acrocianosis iatrogénica - Susana Travassos Cunha; Catarina Pereira (Sociedade Galega de Medicina Interna, 2019)
Sixty-year-old woman, with a history of gastric neoplasia in remission 5 years ago, and since then have a totally iimplantable central venous catheter (TICVC) in the right subclavian vein. No other relevant history and no known allergies.